Evaluasi Pelaksanaan Metode Behaviour Based Safety dalam Membentuk Perilaku Aman Tenaga Kerja pada PT. XYZ - Nayla Iqmalia Dwi Alika; Ahmad Hidayat Nurwahid Hasyim; Helmi Asril Rayhandi Putra; Octa Putri Febrina Salsabila; Moch Meziedane Febri Muzaranu; M Ali Mahfud; David Alik Salinding; Anis Rohmana Malik (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
In an effort to create a safe and productive work environment, the Behavior Based Safety (BBS) approach has become one of the main strategies in occupational safety management, especially in high-risk industries such as logistics. This study aims to evaluate the effectiveness of the implementation of the Behavior Based Safety (BBS) method in shaping the safe behavior of workers at PT XYZ, a logistics company in Balikpapan. The BBS method is an occupational safety approach that focuses on individual behavior in preventing work accidents. This study uses a qualitative method with a descriptive approach through direct observation and interviews with management and workers. The results of the study indicate that the implementation of BBS at PT XYZ has not been running optimally. Some of the main obstacles found include the lack of standard operating procedures (SOPs), lack of occupational safety training, weak communication between management and workers, and minimal involvement of workers in a safety culture. Although there is a commitment from management, improvements are still needed in the aspects of socializing safety policies, providing written documents, and ongoing training to build a safe and sustainable work culture.